Структурні зміни у системі електронних станів шаруватого кристала, деформованого зсувом шарів - Stakhira, Y. M.; Stakhira, R. Y. (Publishing house "Academperiodika", 2018)
Changes in the structure of electron states in a layered crystal induced by a deformation giving rise to a relative shift of the layers have been analyzed. It is shown that if the deformation force has a low-frequency harmonic component, the period of the deformed lattice changes discretely, and the energy degeneration of the electron states becomes partially eliminated. A space-time deformation removes the energy degeneration for states, whose wave vectors have a component normal to the layer plane and equal to the component of the reciprocal lattice period in the deformed crystal along this direction. It also generates a discontinuity in the functional dependence of the energy on this component. Within a separate time period of perturbation, the energy degeneration becomes eliminated at different time moments, at which the lattice period along the shear direction is a multiple of the shift. The energies within this time interval can be identified with the use of a radio equipment, by detecting the time moments, when the density of electronic states drastically changes.